2015
DOI: 10.1186/s13018-015-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bisphosphonates in preventing femoral periprosthetic bone resorption after primary cementless total hip arthroplasty: a meta-analysis

Abstract: BackgroundBone loss leading to aseptic loosening of the prosthesis and periprosthetic fracture is a mode of failure in cementless total hip arthroplasty (THA). The aim of this meta-analysis was to evaluate the effect of bisphosphonates in preventing femoral periprosthetic bone resorption following primary cementless THA zone by zone.MethodClinical randomized controlled trials concerning bisphosphonates application after primary cementless THA published up to October 2014 were retrieved from PubMed, Cochrane li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…Thus, we could not conclude that risedronate had a significant influence on bone loss among patients with only THA. Zhao et al [ 1 ] conducted a similar meta-analysis about bisphosphonates for bone loss after THA; however, only one study comparing risedronate versus placebo was included in the meta-analysis. Therefore, large-scale trials are required to validate the effects of risedronate focus on patients with THA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we could not conclude that risedronate had a significant influence on bone loss among patients with only THA. Zhao et al [ 1 ] conducted a similar meta-analysis about bisphosphonates for bone loss after THA; however, only one study comparing risedronate versus placebo was included in the meta-analysis. Therefore, large-scale trials are required to validate the effects of risedronate focus on patients with THA.…”
Section: Discussionmentioning
confidence: 99%
“…Total hip arthroplasty (THA) has become a popular and successful surgical option for patients with hip osteoarthritis or hip fracture [ 1 ]. Some studies revealed that more than 75% of the revision arthroplasties were performed due to prosthesis loosening and peri-prosthetic fracture, which were accompanied by severe periprosthetic bone loss [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies indicated that BPs had no significant effect on suppressing bone loss after THA [12, 13]. In contrast, previous meta-analyses suggested BPs could inhibit early bone resorption around the implant [1417]. However, these studies only included randomized controlled trials (RCTs) published before 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonates are antiresorptive agent which promotes bone mineralization and inhibits the biological effect of osteoclasts [ 8 ]. Substantial randomized controlled trials (RCTs) have demonstrated its beneficial effect on preserving periprosthetic bone in cementless THA [ 9 ]. Risedronate is a bisphosphonate with potent antiresorptive activity that is used in the treatment of Paget disease of bone and multiple myeloma [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%